Volumes of the Hippocampal Formation Differentiate Component Processes of Memory in a Community Sample of Homeless and Marginally Housed Persons. (8th November 2018) - Gicas, Kristina M; Thornton, Allen E; Waclawik, Kristina; Wang, Nena; Jones, Andrea A; Panenka, William J; Lang, Donna J; Smith, Geoff N; Vila-Rodriguez, Fidel; Leonova, Olga; Barr, Alasdair M; Procyshyn, Ric M; et al.
Abstract: Objective: Persons who are homeless or marginally housed exhibit significant cognitive dysfunction, with memory being the most impaired domain. Hippocampal subfield volumes have been found to differentially relate to component processes of memory. The neural correlates of memory have not been previously examined in marginalized persons who are understudied and underserved. We examined whether hippocampal subfields and entorhinal cortex volumes are uniquely related to indices of verbal episodic memory using the Hopkins Verbal Learning Test – Revised. Method: Data was used from a large sample of community dwelling homeless and marginally housed adults ( N = 227). Regression analyses were conducted to examine hippocampal subfield volumes (CA1, CA3, CA4, dentate gyrus, subiculum) and entorhinal cortex, and their associations with measures of verbal immediate recall, learning slope, and verbal delayed recall. Results: Greater CA3 subfield volume was associated with better performance on an index of encoding (immediate recall), but only in older individuals. Greater CA1 and subiculum volumes were associated with better performance on immediate and delayed recall (measures that tap into retrieval processes), but not with learning slope (a more pure index of encoding). Entorhinal cortex volume was related to all components of memory beyond total hippocampal volume. Conclusions: Our results suggest common neuroanatomical correlates of memory dysfunction in large sample of marginalized persons, and these are uniquely related to different components of memory. These findings have clinical relevance for marginalized populations and theoretical relevance to the growing literature on functional specialization of the hippocampal subfields.